Dynamics of the Moving Load Acting on the Hydro-elastic System Consisting of the Elastic Plate, Compressible Viscous Fluid and Rigid Wall - Akbarov, S. D.; Ismailov, M. I. (TECH SCIENCE PRESS, 2015)
The subject of the paper is the study of the dynamics of the moving load acting on the hydro-elastic system consisting of the elastic plate, compressible viscous fluid and rigid wall. Under this study the motion of the plate is described by linear elastodynamics, and the motion of the compressible viscous fluid is described by the linearized Navier-Stokes equations. Numerical results are obtained for the case where the material of the plate is steel, but the fluid material is Glycerin. According to these results, corresponding conclusions related to the influence of the problem parameters, such as fluid viscosity, plate thickness, fluid depth, fluid compressibility and initial stresses on the inter-phase normal stress and normal and tangent velocities of the fluid caused by the load which moves with constant velocity, are made. In particular, it is established that the influence of the fluid viscosity of the aforementioned quantities becomes more considerable under lower velocities of the moving load. Moreover, it is established that there exists a critical velocity of the moving load under which a resonance type event takes place.
Keywords: Moving load; compressible viscous fluid; metal elastic plate; critical velocity; hydro-elastic system; VIBRATIONS; LAYER; VISCOSITY; WAVES; Computer Science; Materials Science